The Impact of Peer Evaluation on the Quality of nursing report - somayeh akbari farmad (Babol University of Medical Sciences, 2020)
Background and Objective: Peer evaluation has been introduced as a control method and part of nursing quality assurance programs. Peer evaluation is the process by which nurses systematically review, control, and judge the quality of nursing care relative to occupational standards. The aim of this study was to determine the effect of peer evaluation on the quality of nursing reports of evaluated nurses in the surgical wards of Kamali Educational and Medical Center in 2019. Methods: This study is a quasi-experimental interventional study before and after. The research tool is a standard checklist for examining the quality of nursing reports and the study population includes all nurses working in a surgery ward of Kamali Hospital in Karaj with at least two months of experience in this ward. To evaluate the effect of the intervention, the method of registering the evaluated nurses before and after the intervention is evaluated by the researcher. Findings: In this study, 30 nurses (women) participated and 60 checklists were completed by the researcher to review the files registered by the evaluating nurses in surgery ward one, before and after the intervention, and a total of 180 files with standard checklists. The quality of registration in the Cardex and reporting was checked. The results showed that the status of compliance with the principles of reporting (Z = -4.838 Asymp. Sig. (2-tailed): <0.001) as well as the status of compliance with the principles of registration in Cardex and Pharmacy Card (Z = -4.253 Asymp. Sig. (2-tailed)) : <0.001) Improved.